Art and sexual politics: women's liberation, women artists, and art history. - Hess, Thomas B.; Baker, Elizabeth C.; Hess, Thomas B.; Baker, Elizabeth C. (Art news series, 1978)
The growing momentum of the women's liberation movement has stirred controversy and self-examination in all areas of contemporary endeavor—education, business, sciences, politics and the arts. This superb collection of timely, thought-provoking essays provides a rich, multidimensional, view of the prejudices, historical distortions, and inadequacies inherent in the art establishment. The contributors present a harmonious plea for a sincere and unqualified acceptance of women artists in teh contemporary art world.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; antiquité; approches et analyses; arts; cours; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; inégalités; justice sociale; moyen-âge; premier cycle; périodes historiques; sexisme; systèmes d'oppressions; thématiques

Discussions des idées reçues sur les caractères propres à chaque sexe - Wollstonecraft, Mary (Défense des droits de la femme, 1976)
Keywords: 1700-1799; EDI; approches et analyses; cours; discipline; discours dominant; droits des femmes*; europe; fem1000; incontournable; inégalités; premier cycle; périodes historiques; royaume-uni; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; épistémologie